Exploring the impact of the stargazin V143L mutation on the dynamics of the AMPA receptor: stargazin complex - Raquel P. Gouveia; Raquel P. Gouveia; Carlos A. V. Barreto; Carlos A. V. Barreto; Rita Melo; Ana Luísa Carvalho; Ana Luísa Carvalho; Irina S. Moreira; Irina S. Moreira (Frontiers in Cellular Neuroscience)
Stargazin, a transmembrane AMPAR regulatory protein (TARP), plays a crucial role in facilitating the transport of AMPA receptors to the cell surface, stabilising their localisation at synapses and influencing their gating properties. The primary objective of this study was to investigate the effect of the V143L mutation in stargazin, previously linked to intellectual disability, on the interaction between stargazin and AMPA receptors. To achieve this, we conducted a thorough examination of eight distinct molecular dynamics simulations of AMPA receptor-stargazin complexes, each associated with different conductance levels. Through extensive analysis of complex interface structures and dynamics, we revealed that the stargazin V143L mutation had a more pronounced destabilising effect on complexes with lower conductance levels than on the conductive states of the receptor, suggesting a potential association with impaired synaptic transmission in individuals with this mutation.